A challenge to the seven widely believed concepts of COPD - Al-Kassimi, Feisal A (Dove Medical Press, 2013)
This review proposes a critical reassessment (based entirely on published evidence) of the following seven common beliefs about chronic obstructive pulmonary disease (COPD): (1) COPD is one disease. (2) There is a valid definition for COPD. (The current definition includes cases of irreversible asthma and bronchiectasis, and occasionally, other obstructive lung conditions). (3) Irreversible asthma in smokers and COPD cannot be differentiated. (4) A “chronic bronchitis” form of COPD exists and is characterized by blue bloater status and normal carbon monoxide diffusion studies. (5) Phenotyping has no bearing on medication choice in COPD. (6) Computerized scoring of lung attenuation on CT scans can diagnose emphysema. (Emphysema scores overlap in irreversible asthma and COPD); however, qualitative visual changes may be useful for differentiation. (7) A definable entity called the overlap (of COPD and asthma) syndrome exists. Conflict over the abovementioned points denies patients proper phenotype-guided therapy and encourages a multidrug approach to COPD management. The recently coined term, overlap syndrome, invites a double-barreled therapy aimed at asthma and COPD, despite the absence of any agreement about how to define the syndrome and the lack of any related drug trials (in the area of inhaled corticosteroids). A diagnosis of COPD is associated with high morbidity and escalating costs, suggesting the need for a thorough new examination of the evidence.